Analysis of Student Self-Esteem and Anxiety in Writing Thesis during the Covid-19 Pandemic (Nursing Care Journal, 2022)
This study aims to identify the relationship between self-esteem and student anxiety in preparing the final scientific paper and is expected to provide benefits for finding various conditions in students when preparing the final project and can be developed in nursing interventions. The results of the study conducted through interviews with ten Nursing undergraduate students, STIKES Guna Bangsa showed that students in composing a thesis felt anxious. Six people were moderately anxious, three people were very anxious, and one was mildly anxious. The results of the interview also revealed that the ability of students in writing thesis answers to students varied, two students were confident and confident, eight students felt unable to compile a thesis. To know relationship between self-esteem with anxiety in preparing a thesis on the students. This research was a quantitative descriptive research with cross sectional approach. This research involved 58 students. The study instrument used an anxiety questionnaire and Rosenberg's Self-Esteem Scale (RSES). Technique of data analysis used pearson- product moment correlation test. 1) Students‟ self-esteem is mostly in medium category as number of 31 people (53,4%), 2) students‟ anxiety is mostly in medium category as number of 48 people (82,8%), 3) There is corelation between self-esteem and anxiety in making thesis on the students with a significant value of 0.001 (p <0.05). There is a relationship of self-esteem and anxiety of making a thesis on the students.